Kajian Resiko, Dampak, Kerentanan dan Mitigasi Bencana Abrasi Dibeberapa Pesisir Indonesia - Ima Nurmalia Permatasari (Jurnal Riset Kelautan Tropis (Journal Of Tropical Marine Research) (J-Tropimar), 2021)
Coastal areas are areas of sea and land where the region is under pressure due to activities and phenomena that occur on land and at sea. Coastal problems such as coastal morphological changes such as abrasion and accretion occur. Coastal erosion, also known as abrasion, tends to increase in various areas. The cause of coastal erosion itself is Soil Level Drop, land subsidence, mangrove forest damage, damage caused by wave hydrodynamic forces, damage due to other natural causes and damage caused by other human activities. Some factors of disaster risk include the high impact of extreme wave threats and coastal abrasion, the high vulnerability of a region, and the low capacity to face the threat of disasters. Abrasions make residents lose their homes and farmland and encroachment which has resulted in loss of livelihood and reduced income. Today the majority of productive-aged people have a livelihood as factory workers and construction workers. The vulnerability value of an area is influenced by several factors, namely the high density of residents and vulnerable groups, the high number of poor families and fishing groups, the high density of settlements and the lack of vegetation of coastal areas in the face of disaster threats. One of the mitigations carried out is knowing the extent of damage due to abrasion, Knowing the distribution of abrasion areas and abrasion disaster mitigation with community-based coastal area management and integrated coastal management.